COMBINING ABILITY AND HETEROSIS OF CHILLI (Capsicum annuum) RESISTANCE TO ANTHRACNOSE - Yulia Irawati; Sriani Sujiprihati; Widodo - (Pusbindiklat - LIPI, 2012)
Anthracnose (Colletotrichum acutatum) is considered as the major disease in chilli. Resistant variety isimportant for controlling infection of disease, since fungicide application and other cultural controlled methodswere not effective. The aim of this research was to estimate combining ability and heterosis of chilli resistanceto anthracnose. Set population of half diallel crosses which involved 6 parents and 15 crosses with C. acutatumisolate BKT 04 were used in this experiment. Mature green fruit were inoculated using a microinjection method.Disease resistant percentage and lesion diameter were used for estimating of combining ability. Disease incidenceand lesion diameter were used for estimating heterosis. General combining ability of IPB C15 was high for diseaseresistance percentage and lesion diameter. Specific combining ability of IPB C15 x IPB C9 was high for diseaseresistance percentage and specific combining ability of IPB C15 x IPB C10 and IPB C4 x IPB C2 were high forlesion diameter. Negative heterosis was expected in disease resistance traits; IPB C15 x IPB C9 had negativeheterosis for disease incidence and IPB C10 x IPB C9 had negative heterosis for lesion diameter.